Developing a Recipe Chatbot: Integrating Regular Expressions with the Tasty API for Enhanced Culinary Information Retrieval - Atqiya, Firas; Suharsih, Ririn; Sholahuddin, Muhammad Rizqi (Universitas Pendidikan Indonesia (UPI), 2024)
This paper explores the development of a recipe chatbot that leverages regular expressions and the Tasty API to provide users with a seamless and intuitive culinary information retrieval experience. By combining the power of natural language processing techniques with a vast recipe database, the chatbot aims to enhance user interaction and provide accurate and relevant recipe recommendations and cooking instructions. The system employs regular expressions to interpret user queries, enabling flexible and natural language input. Integration with the Tasty API allows the chatbot to access a wide range of recipes and detailed information, including ingredients, instructions, and nutritional values. The chatbot's performance is evaluated based on its accuracy in understanding user requests and providing relevant information. This research highlights the potential of combining regular expressions and APIs in developing intelligent chatbots for specific domains, such as culinary arts.